Metric Knowledge of a Selected Population of Students Enrolled in Home Economics Classes - Collins, Jan T. (University of Wisconsin-Stevens Point, 1975)
The purpose of this study was to evaluate the metric knowledge of students enrolled in on-campus home economics classes at the University of Wisconsin-Stevens Point. The historical background of the metric controversy in the United States was also investigated along with the implementation of metrics in the food area. The metric questionnaire which was formulated was administered to 47 students. The hypothesis developed which was tested statistically was that there is no significant difference in the working knowledge of the metric system between categories of students enrolled in home economics classes at the University of Wisconsin-Stevens Point. These categories being age in years, academic major and year in college. Using F-ratio tests, it was proven that there was no significant difference in the working knowledge of the metric system of students and (a) age group, and (b) year in college. A significant difference was proven to exist in the working metric knowledge of the sample and academic majors.